Implementation of Spatio-Temporal Analysis for Land Use Management and Urban Planning in North Halmahera Regency - Yerik Afrianto Singgalen (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
This study aims to examine the attributes of spatio-temporal dynamics and the progression of land-use alterations, which is imperative for comprehending and appraising the condition and transformation of ecosystems. When employed in the context of North Halmahera Regency, this analysis can furnish fundamental insights to facilitate informed decision-making in urban planning. By understanding the spatio-temporal dynamics of land use change in the region, decision-makers can make more effective choices regarding infrastructure development, resource allocation, and sustainable urban growth, ultimately leading to more resilient and well-planned urban environments. In the methodology section, this study employed Landsat 8 OLI satellite imagery and Geographic Information System (GIS) technology to investigate the spatio-temporal dynamics and land use changes in North Halmahera Regency from 2013 to 2023. These Research Findings show that land use management for urban planning objectives should assess several dimensions, such as preserving Hibualamo cultural values, settlement patterns derived from household livelihood assets, and Tobelo City's economic activities.